I've had a good life, what's left is a bonus: Factor analysis of the Mental Adjustment to Cancer Scale in a palliative care population. (March 2014) - Goodwin, Laura; Price, Annabel; Lee, William; Rayner, Lauren; Moorey, Stirling; Monroe, Barbara; Sykes, Nigel; Hansford, Penny; Higginson, Irene J; Hotopf, Matthew
Background: The Mental Adjustment to Cancer Scale is an assessment tool commonly used to measure coping in cancer patients, which characterises adaptive coping under the label of 'fighting spirit'. Aim: This study explores adaptation in patients with advanced cancer, by examining the factor structure of the Mental Adjustment to Cancer Scale. Further aims were to examine associations between types of coping and psychological outcomes measured at the same time (time 1) and 4 weeks after referral to palliative care services (time 2). Design: A cross-sectional study with a follow-up assessment 4 weeks later. Factor analysis examined the structure of the Mental Adjustment to Cancer Scale at time 1. Setting/participants: A total of 275 patients with advanced cancer receiving palliative care, of whom 193 took part at follow-up. Results: This study provided evidence for the internal consistency and validity of a new scale of 'acceptance and positivity' for use in advanced cancer patients. Patients with a desire for hastened death had lower acceptance and positivity, and patients with higher global quality of life reported a higher level. Social support was positively associated with acceptance and positivity. Higher scores on the acceptance and positivity scale were associated with reduced odds of a desire for hastened death at time 2. Conclusion: Adaptation to advanced cancer differs from adaptation to early stage cancer, comprising a general acceptance of the illness and trying to make the most of the time that is left. Individuals with low social support were less likely to evidence appropriate adaptation to their illness.